Nanostructured materials - Wilde, Gerhard (Elsevier, 2009)
This book focuses on functional aspects of nanostructured materials that have a high relevance to immediate applications, such as catalysis, energy harvesting, energy storage, optical properties and surface functionalization via self-assembly. Additionally, there are chapters devoted to massive nanostructured materials and composites and covering basic properties and requirements of this new class of engineering materials. Especially the issues concerning stability, reliability and mechanical performance are mandatory aspects that need to be regarded carefully for any nanostructured engineering material.
Keywords: Nanostructured materials.; elektronické knihy; electronic books